2020
DOI: 10.1002/er.5214
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on modeling and performance optimization of Stirling engine

Abstract: Summary Modeling with optimization has become a ubiquitous practice in the field of Stirling engine. A plethora of studies in the literature is dedicated in developing a feasible optimized model that can precisely predict the performance of Stirling engine. Hence, the purpose of this article is to compile and expansively review the thermodynamic models and optimization efforts made in pursuit of performance enhancement of the Stirling engine. An extensive range of models available in the literature is painstak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 98 publications
(168 reference statements)
0
26
0
1
Order By: Relevance
“…There is one power piston and one displacer piston in the beta and gamma type Stirling engines. The difference between beta and gamma Stirling engine is that in beta type both the pistons are located in same cylinder where as in gamma Stirling engine both pistons are located in separate cylinders 42 …”
Section: Design Development and Performance Evaluation Of Csp‐dssmentioning
confidence: 99%
“…There is one power piston and one displacer piston in the beta and gamma type Stirling engines. The difference between beta and gamma Stirling engine is that in beta type both the pistons are located in same cylinder where as in gamma Stirling engine both pistons are located in separate cylinders 42 …”
Section: Design Development and Performance Evaluation Of Csp‐dssmentioning
confidence: 99%
“…Due to the external combustion feature, harmful exhaust emissions such as hydrocarbon (HC), carbon monoxide (CO), and carbon dioxide (CO 2 ) are much less and controlled compared to internal combustion engines. 17,18 Various power generation methods and machines are developed to meet energy demands using renewable energy sources. Stirling engines, one of these alternative power generating machines, can easily use many renewable energy sources due to their external combustion feature and have again taken their place at the top of the energy generation required due to positive developments in production technology compared to other power generation systems.…”
Section: Introductionmentioning
confidence: 99%
“…Multi‐objective optimizations were performed considering the engine efficiency, output power, and power per unit investment cost as the objective functions. Recently, Ahmadi et al 31 and Ahmed et al 32 have comprehensively reviewed various analytical modeling and performance optimization techniques that were applied to assess the Stirling heat engine. The authors have concluded the polytropic FST model as the better model for the numerical analysis and the PSO algorithm as the better technique for the optimization.…”
Section: Introductionmentioning
confidence: 99%